Three notes on the neoliberal city in Costa Rica (1980-2017) - Montes Ruiz, Ana Paula (Universidad de Costa Rica, 2018)
The essay explores the emergence of the neoliberal city in Costa Rica within the sociopolitical context that has made it possible during the last thirty-seven years. In doing so, the text has been worked on three ideas: i) the processes of deep neoliberalization in which the State has not been weakening but instead rescaling to economic opening to attract direct foreign investment ii) the socio-spatial restructuring processes of the Great Metropolitan Area that affect the polarization of the development of the city on an east-west axis; and iii) the intensification processes of the urban real estate market.Keywords: neoliberal city; contextualism; Costa Rica; neoliberalization.